Perlindungan Hukum Korban Penipuan Undian Berhadiah Menurut Undang-undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Kadek Yogi Pratama Putra; A Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum, Universitas Warmadewa, 2021)
The development of the times is always followed by technological developments, digital technology has brought a major influence on human life. One example is information and communication technology. Various types of cell phones with the sophistication they have have changed the way humans exchange information and communicate. Various features are available in cellular phones, one of which is the short message service feature or commonly known as SMS. Initially this feature was used to make it easier for humans to send and receive short messages. Over time the feature or short message service is used by criminals for personal gain. Crime in the digital world is called cybercrime. Therefore, the purposes of this study are to examine the legal arrangements for victims of sweepstakes fraud through short message services and reveal forms of legal protection for victims of fraud through short message services. This research is designed with normative legal research using a legal and conceptual approach. Sources of data used are primary and secondary legal data collected using the literature study method. After the research data is collected, the final stage is processing and analyzing the data in a qualitative descriptive manner. The results of the study reveal that the crimes committed by the perpetrators are criminal acts of fraud which have been regulated in article 378 of the Criminal Code and have also been accommodated in the ITE Law which is regulated in article 28 paragraph (1). Furthermore, the victim has legal protection as regulated in the ITE Law.